PENGARUH TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) UNTUK MENGATASI THANATOPHOBIA PADA LANSIA [THE EFFECT OF SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) THERAPY FOR OVERCOMING THANATOPHOBIA IN THE ELDERLY] - Siti Nuroh (Acta Islamica Counsenesia: Counselling Research and Applications, 2022)
This study aims to determine how much influence SEFT therapy has in overcoming thanatophobia in the elderly. The method used is a quantitative method using an associative approach. Collecting data in this study using observation, questionnaires, interviews, and literature study. The results of this study indicate that the effect of SEFT therapy to overcome thanatophobia in the elderly congregation of the Nurul Ikhsan Mosque has a correlation of 69.8% which can be said to be quite high. Based on the regression coefficient test, the Sig value is 0.012 0.05, meaning that there is an effect of SEFT therapy to overcome thanatophobia in the elderly congregation of Masjid Nurul Ikhsan. After therapy, it can be seen that there is a decrease in the level of anxiety towards death, in this case the anxiety in the high category decreases by 62%, in moderate anxiety there is a decrease by 80%, and in the mild anxiety level there is a decrease of 100%.